Peran Teknologi dan Akses Modal dalam Mendorong Pemberdayaan Ekonomi Masyarakat Pesisir - Lusia Lestina Halawa; Evlin Limbong; Jaujari Helmi; Nada Aisyakamila Ramadani; Firman Firman (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
Economic empowerment of coastal communities in Indonesia is essential to improve welfare and reduce social inequality. This study explores the role of technology and access to capital in driving economic empowerment in coastal areas. The method used is a literature study to analyze how technology improves productivity, and how access to capital supports business development. The results of the study show that the use of information and communication technology, as well as inclusive savings programs, have made significant contributions to increasing income and quality of life in coastal communities. Challenges such as poor infrastructure and limited education need to be addressed to achieve full potential in economic empowerment.